Joomla for beginners - Gentles-Jones, Janice; Safari eBooks ([S.l.] : LearnToProgram, 2014)
"Janice's Joomla for Beginners course will teach you everything you need to know about creating, operating and maintaining a Joomla website. With clear examples and engaging lab exercises, you'll go through the Joomla framework step-by-step. From setting up the Joomla environment to creating your own modules, this course has you covered! "--Resource description page.
Title from resource description page (viewed June 19, 2014).
Presenter, Janice Gentles-Jones.
Keywords: Joomla! (Computer file); Web site development; Web sites -- Design; Electronic books